Habilidades profesionales y calidad de servicios en la empresa Aqua Expeditions SAC, 2020 - Morey Mauro, Francisco Jose (2021)
The general objective of this research is to determine the relationship between professional skills and quality of service in the company Aqua Expeditions SAC, 2020. In this descriptive and correlational study, of non-experimental design, a sample of 319 people has been taken out of a population of 2 357 clients. For this purpose, the survey technique and the questionnaire have been the data collection instruments. As a final deduction from this work, it can be stated that the collaborators demonstrate skills for the development of their work, such as the skills for planning and organizing their daily tasks regarding the functions of their position. In the same way, each of them shows to be responsible with the assigned functions, also demonstrating the ability to be creative; and on its own initiative, satisfy the needs and requirements of the client. The quality of the service is good, since the company has technological equipment. The presentation of the staff, properly uniformed, is consistent with the functions and interpersonal relationships that they maintain on a daily basis. In addition, the staff shows professionalism and interest in the satisfaction of the tourist, of the company and how to function in these. Finally, it is determined that there is a relationship between professional skills and quality of service in the company Aqua Expeditions SAC, in 2020, a decision that has been contrasted through a significance of 0.000 and corroborated a correlation coefficient of 0.711 the which is moderate positive.